METHODOLOGY OF CALCULATING ENERGY RELEASED IN NUCLEAR REACTIONS - Urazov Sh; Jo’rayev X; Ergashev B (Журнал естественных наук, 2021)
This article describes the nuclear chemical processes that take place in nuclear reactions, the nature of nuclear reactions, radioactive elements and radioactive formulas.